Strategies for Educational Quality Management in the Digital Transformation Era: A Case Study of SMP PGRI 1 Semarang - Haidar Rohbiyatun; Wiwik Widayati; Titik Haryati (STKIP Taman Siswa Bima, 2025)
The digital transformation era requires schools to adapt their approaches to quality management. However, many schools have not yet optimized the use of data for informed decision-making, particularly in utilizing platforms such as the Education Report (Rapor Pendidikan). This indicates a gap between the availability of digital data and its practical application in school-level quality management. This study aims to analyze educational quality management strategies at SMP PGRI 1 Semarang through the implementation of the Education Report in the digital era. A qualitative approach with a case study method was employed. Data were collected through in-depth interviews with eight key informants, direct observations, and document analysis conducted between January and May 2025. The findings reveal that the use of the Education Report improves transparency, accountability, and the effectiveness of quality management. The platform provides comprehensive data on students’ literacy, numeracy, and character development, enabling more targeted evaluations and planning. Most students reached a “Sufficient” level in literacy and numeracy, though the “Critical Thinking” dimension of character development still requires attention. Key challenges include limited IT infrastructure, platform complexity, resistance to change, and insufficient human resource capacity. This study addresses a research gap regarding school-level data-driven quality management practices and recommends strengthening digital capacity, documentation systems, and multi-stakeholder collaboration to enable schools to become adaptive and sustainable models of data-based quality management in the digital age.